1975
DOI: 10.1073/pnas.72.1.113
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of replication of normal adrenocortical cells in culture by adrenocorticotropin.

Abstract: Adrenocorticotropic hormone (ACTH) 160-180 g) were anesthetized with Nembutal, and the adrenal glands were aseptically removed from surrounding fat, trimmed, bisected, and decapsulated. The tissue was then minced and collected in a sterile 50-ml capped conical polypropylene tube containing 15 ml of phosphate-buffered saline at room temperature. The phosphate-buffered saline solution was removed and replaced with 15 ml of a sterile solution of medium 199 with Earle's salts containing collagenase (4 mg/ml) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
47
2
3

Year Published

1977
1977
2014
2014

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 141 publications
(58 citation statements)
references
References 23 publications
(14 reference statements)
6
47
2
3
Order By: Relevance
“…Physiological ACTH levels are unable to induce compensatory adrenal hyperplasia after unilateral adrenalectomy in hypophysectomized animals (52). In vitro, inhibition of adrenal cell proliferation by physiological ACTH concentrations has been reported, and even pharmacological doses of ACTH induce only moderate cell growth (53). In accord with this findings, activating point mutations of neither the ACTH receptor nor the a-chain of Gs have been identified in benign or malignant adrenocortical tumors (50, 54±56).…”
Section: Acth-receptor Mutations In Adrenal Tumorssupporting
confidence: 67%
“…Physiological ACTH levels are unable to induce compensatory adrenal hyperplasia after unilateral adrenalectomy in hypophysectomized animals (52). In vitro, inhibition of adrenal cell proliferation by physiological ACTH concentrations has been reported, and even pharmacological doses of ACTH induce only moderate cell growth (53). In accord with this findings, activating point mutations of neither the ACTH receptor nor the a-chain of Gs have been identified in benign or malignant adrenocortical tumors (50, 54±56).…”
Section: Acth-receptor Mutations In Adrenal Tumorssupporting
confidence: 67%
“…We have also confirmed that apart from the effect of CER and desCER on adrenocortical steroidogenesis, both polypeptides directly inhibit proliferative activity of the studied cells (20). Thus, as far as proliferative activity is concerned, both CER and desCER have ACTH-like effects, which are known to directly inhibit mitotic activity of adrenocortical cells (38,39).…”
Section: Discussionsupporting
confidence: 64%
“…Adrenal glands from adult male Sprague-Dawley rats (350-400 g) were decapsulated and digested with collagenase and DNase as described (13). The cells were suspended in medium 199 containing 10% fetal bovine serum and 0.004% garamycin (Schering) at a concentration 7.5 X 105 cells per ml and incubated overnight (18 hr) in sterile bacterial Petri dishes (no.…”
Section: Methodsmentioning
confidence: 99%